Clinical study of bronchial asthma in children aged 5 to 12 years with special reference to peak expiratory flow rate - K., Srinivasa; C. B., Ushakiran; Rudrappa, Sudha (International Journal of Contemporary Pediatrics, 2017)
Background: Asthma is one of the most common chronic diseases worldwide imposing a substantial social burden on both children and adults. Over the last 20 years its prevalence has considerably increased, especially among children. The aim of present study is to study the clinical features of bronchial asthma and to assess objective response of PEFR to bronchodilator therapy. Methods: After taking detailed history, clinical examination, the PEFR was recorded in fifty symptomatic bronchial asthma children between 5-12 years of age group before and after salbutamol nebulization. They were compared with PEFR values of normal children from same population in same age group, height range, weight range and sex. Results: Among Fifty cases studied, maximum number (44%) of cases of asthma was found in the age group of 11-12 years with male: female ratio 1.77:1. Cough and wheeze were predominant symptom and was present in all cases (100%). Cold air in 24 (48%) cases, URTI in 15 (30%) cases, dust in 8 (16%) cases and cold food in 3 (6%) cases were found to be important precipitating factors. There was significant reduction in PEFR (L/min) in study group as compared with control group. The percentage of improvement in PEFR was 21.3% after bronchodilator therapy which is statistically significant (P<.000). Conclusions: Significant improvement in PEFR following bronchodilator therapy indicates its usefulness in monitoring the response to treatment of asthma and however serial recording of PEFR is recommended for better management and control of asthma in childhood.